Impact of Learning From Home: Cognitive Development of Early Childhood Education Student in Pandemic Covid – 19 - Tria Wahyuningrum; Lida Khalimatus Sa’diya (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this research was to determine how the covid-19 epidemic affected early childhood cognitive development. Principals, instructors, parents, and students served as informants in this study. The data collection techniques used in this study were inquiry in interview which were carried out to find out several things related to the impact of Covid-19 on students' cognitive development. The descriptive qualitative method was employed to analyze the data. The findings revealed that the cognitive development students during online learning during the Covid-19 pandemic, fell into the capable and quite capable categories in terms of problem-solving skills, logical thinking skills, and symbolic thinking skills. students' cognitive development is achieved because teachers make every effort to give learning materials or tasks that encourage students' cognitive development. The presence of certain parents who are less supportive or do not participate in the online learning system has another impact on children's cognitive development. Students do not do the assignments given by the teacher because there is no guidance due to busy parents so that there are differences in cognitive development between one student and another